SOSIALISASI K3 KELISTRIKAN RUMAH TANGGA DAN UPAYA PENGHEMATAN ENERGI DI DESA KULURAN KECAMATAN KALITENGAH KABUPATEN LAMONGAN - Zainal Abidin; Affan Bachri; Arief Budi Laksono (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
Socialization and counseling k3 and effort in saving energy to the village community is so public got insight and knowledge of security and safety work ( k3 ) in care and maintenance installation houses and make maximum savings in. electrical power consumptionSocialization the very enthusiastic in the event discussion and particular case k3, electricity a video and several efforts energy savings can be done in the community.